Weak-lensing halo numbers and dark-matter profiles - Bartelmann, Matthias; King, Lindsay J.; Schneider, Peter (Arxiv, 2008)
Integral measures of weak gravitational lensing by dark-matter haloes, like the aperture mass, are sensitive to different physical halo properties dependent on the halo mass density profile. For isothermal profiles, the relation between aperture mass and virial mass is steeper than for haloes with the universal NFW profile. Consequently, the halo mass range probed by the aperture mass is much wider for NFW than for isothermal haloes. We use recent modifications to the Press-Schechter mass function in CDM models normalised to the local abundance of rich clusters, to predict the properties of the halo sample expected to be accessible with the aperture mass technique. While ~10 haloes should be detected per square degree if the haloes have NFW profiles, their number density is lower by approximately an order of magnitude if they have isothermal profiles. These results depend only very mildly on the cosmological background model. We conclude that counts of haloes with a significant weak-lensing signal are a powerful discriminator between different dark-matter profiles.
Gesehen am 27.09.2017